Gated discrimination of the stem signal in pulsed radiation fields for a fiber optic dosimetry system based on the radioluminescence of beryllium oxide. (November 2017) - Teichmann, T.; Sponner, J.; Radtke, J.; Henniger, J.
Abstract: In this work the stem-removal by gated detection of radioluminescence signals in pulsed radiation fields is applied to a BeO-based fiber optical dosimetry system for the first time. The short luminescence life time of BeO, which is around 27 μs at room temperature, requires a fast detection system. Measurements with 10 ns temporal resolution have been carried out in different radiation fields of a medical linear accelerator within a mean dose rate range of 33–550 cGy/min and for field sizes of 10 × 10 and 34 × 34 cm 2 . The influence of the dose rate and the length of irradiated light guide on the temporal signal shape of the luminescence have been investigated. Based on the information of the raw data, methods to remove the stem part of the signal in real time have been tested. Highlights: Dose rate measurements with radioluminescence of BeO in pulsed radiation fields. Two decay components of radioluminescence comparable to OSL emission. Time stamp raw data with 10 ns resolution. Methods for time based stem discrimination with BeO. Reduction of stem effect in real time to 1/50.